History of HPV in HPV-positive elderly women - Hermansson, Ruth S.; Lillsunde-Larsson, Gabriella; Helenius, Gisela; Karlsson, Mats G.; Kaliff, Malin; Olovsson, Matts; Lindström, Annika K. (European journal of obstetrics & gynecology and reproductive biology: X, 2024)
The aim of this study was to examine the natural course of HPV infection in women of 60 years and older who were HPV positive at inclusion, and any association between HPV positivity in historical samples and dysplasia outcome. Eighty-nine women aged 60–82 years, who tested positive for HPV between 2012 and 2016 were included. Sampling for cytology and/or histology was also performed. HPV genotyping was carried out on archived material back to 1999. Of the 89 HPV-positive women 16 had HSIL, 34 had LSIL and 39 were benign at inclusion. Of the women with HSIL, 50.0% had the same HPV type in the archive samples, 12.5% had another type, and 37.5% were HPV negative. Among the 34 women with LSIL, 47.1% had the same HPV type in archive samples, 5.8% had another type, and 47.1% were HPV negative. Of the 39 women without dysplasia at inclusion, 25.6% had the same HPV type in archive samples, 5.1% had another HPV type and 69.2% were HPV negative. Surprisingly few of the elderly women thus seem to have a history with the same or any HPV infection the years before being diagnosed with an HPV infection and dysplasia. The significance of an HPV infection for dysplasia development in elderly women is still not fully understood.